Characterization of Cosmos (Cosmos spp.) Accession from The Special Region of Yogyakarta and Riau Origin - Mhd Irfan Hilmi; Taryono Taryono; Rahmi Sri Sayekti (Agrotechnology Innovation Center, Universitas Gadjah Mada, Yogyakarta, 2020)
Cosmos has the potential to be developed as an alternative vegetable. Less characterization and evaluation of cosmos become obstacles in the process of its development. Characterization is the process of observing and identifying the physical, biological, and chemical properties of plants that aim to determine the characteristics of a plant. The purpose of this research is to ind the characteristics of each accession of Cosmos spp. and get accession of Cosmos spp. which has the potential to be developed or used as varieties material assembly. The research was conducted at the AIC (Agrotechnology Innovation Center) of Universitas Gadjah Mada in March-July 2019. The planting material used for this study was the collection of seeds of PIAT UGM from the Special Region of Yogyakarta and Riau. Fifteen cosmos accessions came from DIY and the other 18 came from Riau. Thirty-three accessions have diverse characteristics especially lower colours that are divided into 7 groups of lower colours namely yellow, gold, light orange, orange, pink, purple, and white. Accession number 39 has a rare white colour lower